Aging and productivity: Evidence from piece rates - Tuomas Pekkarinen; Roope Uusitalo (Institute for the Study of Labor (IZA), 2012)
We evaluate the effects of aging on productivity using piece-rate earnings as a proxy for worker output. Our data contain the population of Finnish blue collar workers in 61 different industries during 1990-2002. A unique feature of the data is that we can observe the exact hours worked on piece rates and on fixed time rates as well as earnings under both performance schemes. We account for the selection into piece rates by using firm-level changes in pay systems as instruments for the probability of working on piece rates. A subset of workers also receive both piece rates and time rates within the same quarter. For these workers, we can directly compare the age profile of hourly earnings under piece rates and fixed rates. The results indicate that productivity increases with age until age 40 after which it stays roughly constant. Wage growth is faster than productivity growth for young workers but after age 40 both wages and productivity grow approximately at the same rate.
Keywords: J1; J24; J33; 330; piece rates; productivity; aging; Arbeitsproduktivität; Altersgruppe; Akkordlohn; Alternde Bevölkerung; Schätzung; Finnland